Physicians’ Choice in Using Internet and Fax for Patient Recruitment and Follow-up in a Randomized Controlled Trial - Rahman, M.; Morita, S.; Fukui, T.; Sakamoto, J. (Methods of Information in Medicine, 2004)
Objective: To examine the physicians’ preference between Web and fax-based remote data entry (RDE) system for an ongoing randomized controlled trial (RCT) in Japan.Methods: We conducted a survey among all the collaborating physicians (n = 512) of the CASE-J (Candesartan Antihypertensive Survival Evaluation in Japan) trial, who have been recruiting patients and sending follow-up data using the Web or a fax-based RDE system. The survey instrument assessed physicians’ choice between Web and fax-based RDE systems, their practice pattern, and attitudes towards these two modalities.Results: A total of 448 (87.5%) responses were received. The proportions of physicians who used Web, fax, and the combination of these two were 45.9%, 33.3% and 20.8%, respectively. Multivariate logistic regression analyses revealed that physicians 55 years or younger [odds ratio (OR) = 1.9, 95% confidence interval (CI) = 1.1-3.3] and regular users of computers (OR = 4.2, 95% CI = 2.1-8.2) were more likely to use the Web-based RDE system.Conclusions: This information would be useful in designing an RCT with a Web-based RDE system in Japan and abroad.
Keywords: Randomized controlled trial; Web; fax; physicians’ choice; patient recruitment